THE OPEN BOOK EXAMINATION - Mohd Suhaimy, Khairul Azman; Mohd Salleh, Berhannudin; Esa, Ahmad (Journal of Techno-Social, 2012)
The purpose of this study is to identify student’s perception about the effectiveness of the open book examination and their achievement in such exam as compared to close book examination. Using stratified sampling, 995 students with experience in open book examinations at Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHO) were chosen as respondents. The instrument was a set of questionnaire. The instrument included questions of this study is a set of open book examination and close book examination and the students’ marks for both examinations. SPSS statistical software was used to record the data and several analyses was done, using descriptive and inferential statistics methods such as mean, standard deviation and T-test based on objectives and hypotheses that had been determined. The results show that the students have positive reaction towards open book examination. The results also show that through open book examination students’ achievement was better compared to close book examination.